ANALYSIS OF ENGLISH PHRASEOLOGICAL UNITS OF LITERARY ETYMOLOGY - Kiyаsоvа Rа’nо (Журнал иностранных языков и лингвистики, 2023)
The article analyzes the English phraseology units created by masters of the word and famous writers who used them in their creative works.